Realizing The Intelligent Community In Physical Rehabilitation For COVID-19 Survivors (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
COVID-19 patients who have been declared cured may experience residual symptoms such as fatigue, shortness of breath, impaired mobility, problems in activities of daily living, and insomnia. Unresolved sequelae can lead to long-term disability, so physical rehabilitation is important to improve the functional capacity. This community service activity aims to increase public knowledge about physical rehabilitation after COVID-19. The activity was carried out by providing blended education to 13 offline and 125 online participants. The material was divided into 4 sub-topics, physical exercise, nutrition to increase immunity, herbs and supplements to increase immunity, and prevention of COVID-19 reinfection. Education was carried out using lecture, discuss, and demonstrations. Various media such as powerpoint, video, banner, brochure, and leaflet are also used. Pre-test and post-test were conducted using a questionnaire as a form of evaluation. The results obtained, of the 78 participants who filled out the questionnaire, 49% of them had less knowledge during pre-test and turned into 100% good knowledge at the post-test. After the education, participants also able to practice physical exercises, use masks properly, and wash their hands according to the material provided. Based on these results, it can be concluded that education is effective in increasing public knowledge.